Relationship between time-varying achieved HbA1c and risk of coronary artery disease events among common haptoglobin phenotype groups with type 2 diabetes: the ADVANCE study - Giuseppe Mancia; Mark Woodward; John Chalmers; Neil Poulter; Eric Rimm; Elizabeth Selvin; Michel Marre; Michelle Samuel; Stephen Harrap; Katie Harris; John Sapp; Leah E Cahill; et al. (BMJ Open Diabetes Research & Care)
Introduction This study sought to determine whether the association between attaining specific glycated hemoglobin (HbA1c) targets (<7.0% (<53 mmol/mol) and ≥8.0% (≥64 mmol/mol) compared with 7.0%–7.9%) over time and risk of incident coronary artery disease (CAD) was dependent on haptoglobin (Hp) phenotype in the Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation (ADVANCE) study.Research design and methods Prospectively collected HbA1c data from the ADVANCE biomarker case-cohort study, updated at 6 months and every 12 months thereafter over a median of 5.0 (IQR 4.5–5.3) years, were analyzed in relation to incident CAD in the Hp2-2 (n=1323) and non-Hp2-2 (n=2069) phenotypes separately using weighted multivariable-adjusted Cox regression models. Additional a priori stratifications by sex, race, previous cardiovascular disease (CVD), and type 2 diabetes duration were performed.Results Mean HbA1c was similar in each phenotype group throughout the study. Compared with HbA1c of 7.0%–7.9%, HbA1c <7.0% was not associated with CAD risk for any phenotype group or subgroup. HbA1c ≥8.0% compared with 7.0%–7.9% over time was associated with higher CAD risk for the Hp2-2 phenotype only (HR 1.53, 95% CI 1.01 to 2.32; no significant association in the non-Hp2-2 type: 1.26, 0.89 to 1.77, p-interaction=0.71); this was pronounced when those with previous CVD at baseline were excluded (Hp2-2: 2.80, 1.41 to 5.53, p-interaction=0.03). Compared with HbA1c of <8.0%, having HbA1c ≥8.0% was associated with a 59% higher CAD risk among participants with the Hp2-2 phenotype (1.59, 1.12 to 2.26) and a 39% higher CAD risk among participants without the Hp2-2 phenotype (1.39, 1.03 to 1.88, p-interaction=0.97).Conclusions The present ADVANCE analysis suggests that not having HbA1c ≥8.0%, rather than achieving HbA1c <7.0%, was found to be particularly important for CAD prevention among people with type 2 diabetes and the common Hp2-2 phenotype. While the subgroup analyses were likely underpowered, their inclusion is hypothesis generating and can be used in future meta-analyses to improve power and generalizability.